MINI RISET SISTEM INFORMASI AKUNTANSI PERANAN SIA DALAM PENGAMBILAN KEPUTUSAN TERHADAP ‘TOKO BU NANCY’ - Tiara Marcella Ruskito (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
The role of Information Systems is really useful to make management determine decision easier, but not with replace it. To determine the final result of a decision is the task of the management company. If the management company made a wrong decision, it will cause a wrong policy that have been set or assigned by the company or the organisation. The application of accounting information systems has been develope . Information Systems is not only use for a big company. It also can be use for a small market.This research was conducted by using quantitative data analysis method. All data that have been obtained based on interview result and all the facts. The purpose of this research is to know about The role of Information Systems in making decision on determination pricing at ‘Toko Bu Nancy’The transaction system of ‘Toko Bu Nancy’ is still using paper to fill all data. Because ‘Toko Bu Nancy’ is small market. That’s why ‘Toko Bu Nancy’ need a system that can help processing all data and transaction.Based on this research, actually the accounting information system at ‘Toko Bu Nancy’ can be said quiet good. Because the price that been determinate are the same with another market. Even though ‘Toko Bu Nancy’ is still a small market, but the accounting information that been recorded is quiet detail so the information that needed in making decision determination pricing can be obtained quick and easily. It can be conclude that ‘Toko Bu Nancy’ has a great and effective accounting information.